The Relations of Effortful Control and Impulsivity to Children's Sympathy: A Longitudinal Study - Eisenberg, Nancy (2007)
The relations of children's (n = 214 at Time 1; M age = 6 years at Time 1) dispositional sympathy to adult-reported and behavioral measures of effortful control (EC) and impulsivity were examined in a longitudinal study including five assessments, each two years apart. Especially for boys, relatively high levels of EC and growth in EC were related to high sympathy. Teacher-reported impulsivity was generally modestly negatively related to measures of teacher-reported sympathy for boys, and a decline in impulsivity was linked to boys' sympathy. Some findings suggested a positive association between impulsivity and children's self-reported sympathy. EC, especially when reported by teachers, was more often a unique predictor of sympathy than was impulsivity. Results generally support the argument that sympathetic individuals, especially boys, are high in EC and that EC is a more consistent predictor of sympathy than impulsivity.